L'État est-il en mesure d'infléchir le «sort» d'une langue? - Kramer, Nataliya (Wydawnictwo Naukowe UAM, 2003)
The author ponders in her article - based mainly on the example of the Norwegian language - whether state's interference through its specialised organs may influence the development and formation of language norms. In conclusion the author claims that only the combination of "language management approach" and "free enterprise style" may give satisfactory results in managing problems of the language.
Can a state influence the "fate" of a language?
Keywords: Norwegian language; Language norms